Penerapan Mudharabah Pada Lembaga Keuangan Syariah - Maksudin; Khoirul Ibad; Fais Abdurahman Nahrowi (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
The problems examined in this study are related to implementation Mudharabah according to Kompilasi Hukum Ekonomi Syariah (KHES) and mekanism Mudharabah in Bank Syari’ah Indonesia. This type of research is qualitative research that builds meaning based on data obtained from the field. The procedure for this qualitative research is processing data which will later produce descriptive data in the form of written and spoken words from people and behavior that can be observed. Data collection was carried out by conducting observations, in-depth interviews and documentation. Data analysis is carried out by giving meaning to the data that has been collected, then from this data a conclusion is drawn. The results of this study reveal that the implementation of mu??rabah in Sharia financial institutions, namely Bank Syari’ah Indonesia has fulfilled and is in accordance with Islamic law and what is contained in it Kompilasi Hukum Ekonomi Syariah (KHES). On BSI implementation of the contract Mudharabah only on collecting funds from customers, namely savings Mudharabah and deposit Mudharabah in the distribution of funds are not used. This is due to the large risks that will be accepted by bank BSI who must bear all losses experienced by customers as capital managers. Then the profit sharing or ratio received must be based on an agreement between both parties and will be received every month and within a predetermined time period.